Preparation and in-Vitro Evaluation of Cinnarizine Raft Forming Chewable Tablets - Aseel S. Najm; Wedad K. Ali (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
Cinnarizine is an anti-histaminic drug and is mainly used to treat symptoms accompanying motion sickness like vomiting and dizziness. It has low and variable bioavailability due to its low water solubility. Cinnarizine (weakly basic drug) is formulated as raft forming